ANALYZING BUSINESS PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES (SMEs) BASED ON HUMAN CAPITAL, SOCIAL CAPITAL AND COMPETITIVE ADVANTAGE - Qamariah, Inneke; Muchtar, Yasmin Chairunisa (Ecoforum Journal, 2019)
Small and Medium Enterprises (SMEs) play an essential part in the development of national economy. It also considered as the main source of employment, poverty reduction, improvement in lifestyle and empowerment of low-income groups. In Indonesia SME also has important role, SME acts as the driving force of economic growth and development. Nevertheless, there are various issues to be addressed for SMEs to improve its performance and competitiveness in the hyper dynamic global business. To encounter the rapid changing, SME should possess the intellectual capital as its strategy management to create continuous competitiveness. The aim of this research is to analyze the effect Human Capital (HC) and Social Capital (SC) on Competitive Advantage, and the role of Competitive Advantage (CA) as the mediator of the relationship between Human Capital (HC) and Social Capital (SC) on Business Performance (BP). The result shows only Human Capital significantly affects the Competitive Advantage of SMEs, while Social Capital does not affect the Competitive Advantage of SMEs. Next, both Social Capital and Competitive Advantage significantly affect the Business Advantage of SMEs, meanwhile human capital does not affect the Business Advantage of SMEs. Moreover, competitive advantage does not mediate the relationship between human capital and social capital to business performance.